2022
DOI: 10.2196/36405
|View full text |Cite|
|
Sign up to set email alerts
|

Using the Transformative Storytelling Technique to Generate Empowering Narratives for Informal Caregivers: Semistructured Interviews, Thematic Analysis, and Method Demonstration

Abstract: Background The transformative storytelling technique is an innovative top-down approach to narrative therapy that aims to provide building blocks for creating flourishing narratives for target groups or populations. This approach acts as a facilitator for implementing the human-centered design in developing digital self-help tools for larger samples or target groups. Objective This study applied the transformative storytelling technique, as a new approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 40 publications
0
8
0
1
Order By: Relevance
“…Carragher et al (2021) used storytelling as a therapeutic approach for individuals living with aphasia and demonstrated an additional role of storytelling in improving aspects of language and communication. Similarly, the authors of this paper (Petrovic et al, 2022) demonstrated the application of storytelling on a sample of informal caregivers. Moreover, in a large-scale digital project exploring the role of storytelling in formal education, storytelling also showed excellent results in supporting the knowledge acquisition in a sample of over 17.000 students, as well as in media literacy, and improvement in attitudes and behaviors of the students (Blas and Paolini, 2013).…”
Section: Storytelling For a Large-scale Supportmentioning
confidence: 80%
See 4 more Smart Citations
“…Carragher et al (2021) used storytelling as a therapeutic approach for individuals living with aphasia and demonstrated an additional role of storytelling in improving aspects of language and communication. Similarly, the authors of this paper (Petrovic et al, 2022) demonstrated the application of storytelling on a sample of informal caregivers. Moreover, in a large-scale digital project exploring the role of storytelling in formal education, storytelling also showed excellent results in supporting the knowledge acquisition in a sample of over 17.000 students, as well as in media literacy, and improvement in attitudes and behaviors of the students (Blas and Paolini, 2013).…”
Section: Storytelling For a Large-scale Supportmentioning
confidence: 80%
“…Informal caregivers are family members or close others who provide long-term care for a loved one in need, with no financial benefit. After exploring the existing digital solutions for informal caregivers (Petrovic and Gaggioli, 2020) and reflecting on how these solutions are used in the caregiving context, we noted a gap in the existing tools for supporting and facilitating the shift into the caregiving role and understanding personal and care related needs throughout the role (Petrovic et al, 2022).…”
Section: Transformative Storytelling Techniquementioning
confidence: 99%
See 3 more Smart Citations